Rapid whole cell imaging reveals a calcium-APPL1-dynein nexus that regulates cohort trafficking of stimulated EGF receptors - H. M. York (Nature Portfolio, 2021)
York et al employ lattice light-sheet microscopy to study the initial events following activation of the epidermal growth factor receptor (EGFR) in whole live cells. They find that APPL1 relocates from pre-existing endosomes, triggered by calcium, to EGFR puncta which results in a cohort, dynein mediated movement of EGFR towards the peri-nuclear region of the cell, expanding our understanding of EGFR trafficking dynamics.